DIAGNOSTIC ACCURACY OF T2 WEIGHTED IMAGING AND GADOLINIUM ENHANCED MRI IN DIAGNOSIS AND STAGING OF URINARY BLADDER CARCINOMA TAKING HISTOPATHOLOGY AS GOLD STANDARDS - MAQSOOD, S; MUGHAL, HH (Biological and Clinical Sciences Research Journal, 2023)
Urinary bladder carcinoma (UBC) diagnosis and staging are critical for treatment planning and patient prognosis. This histopathology-guided study evaluates the diagnostic accuracy of T2-weighted imaging (T2WI) and gadolinium-enhanced MRI (GE-MRI) in UBC diagnosis and staging, with histopathology as the gold standard. A total of 30 patients with suspected or confirmed UBC were included in the study. T2WI and GE-MRI were performed, and imaging findings were compared with histopathological results obtained from transurethral resection of bladder tumor (TURBT) or radical cystectomy specimens. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of T2WI and GE-MRI were calculated. The results demonstrate that T2WI had a sensitivity of 85%, specificity of 80%, PPV of 90%, NPV of 75%, and overall accuracy of 83.3% in diagnosing UBC. GE-MRI showed a sensitivity of 90%, specificity of 85%, PPV of 92%, NPV of 80%, and overall accuracy of 88.3%. Both imaging modalities exhibited high diagnostic accuracy in detecting UBC lesions and staging tumor extent. In conclusion, T2WI and GE-MRI are valuable tools for UBC diagnosis and staging, providing essential information for treatment planning and patient management.